Declining business dynamism in Europe: The role of shocks, market power, and technology - Filippo Biondi; Sergio Inferrera; Matthias Mertens; Javier Miranda (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2024)
We study changes in business dynamism in Europe after 2000 using novel microaggregated data that we collected for 19 European countries. In all countries, we document a broad-based decline in job reallocation rates that concerns most economic sectors and size classes. This decline is mainly driven by dynamics within sectors, size, and age classes rather than by compositional changes. Large and mature firms experience the strongest decline in job reallocation rates. Simultaneously, the employment shares of young firms decline. Consistent with US evidence, firms' employment has become less responsive to productivity shocks. However, the dispersion of firms' productivity shocks has decreased too. To enhance our understanding of these patterns, we derive and apply a novel firmlevel framework that relates changes in firms' sales, market power, wages, and production technology to firms' responsiveness and job reallocation.
Keywords: D24; D43; J21; J23; J42; L11; L25; 330; business dynamism; European cross-country data; job reallocation; market power; productivity; responsiveness of labor demand; technology